Pelatihan Pemanfaatan Buku “Gizi Seimbang Remaja: Cegah Stunting” untuk Meningkatkan Pola Konsumsi Pangan Remaja - Aslis Wirda Hayati; Husnan Husnan; Roziana Roziana (Jurnal Kesehatan Komunitas, 2023)
The prevalence of stunting in the Southeast Asia/South-East Asia Regional (SEAR) is 36.4%. One of the efforts to prevent and reduce the prevalence of stunting is to teach teenagers about food consumption patterns based on balanced nutrition. Community service aims to improve adolescent food consumption patterns. The training was conducted from February to d. August 2022 at SMP N 1 Kampar, Kampar District, Kampar Regency. Assessment of adolescent eating patterns was carried out using pre and post-test questionnaires. Questions related to the type, amount, and frequency of eating. The practice of administering food was carried out 3 times at the Food Processing Laboratory of the Integrated Laboratory of Poltekkes, Ministry of Health, Riau on Jl. Melur 103 Pekanbaru City. Assessment of adolescent skills in food administration was carried out by observing using a checklist. The number of participants in the training was 12 teenagers. The result of the activity is an increase in adolescent food consumption patterns by 6.7% from 82.7 to 89.4%. The increase is seen in the frequency of food consumption from 75% to 80%. The type and amount of food consumed by adolescents before the training appeared to be good with a value above 80%. The average practice of processing a balanced menu for teenagers is in a good category with a score above 80%. The conclusion of this activity is that there is an increase in adolescent food consumption patterns after participating in the Training on the Use of the Book "Balanced Nutrition for Adolescents: Prevent Stunting". The type and amount of food consumed by adolescents were good before the training. The frequency of adolescent food consumption became good after the training.